Forecasting the Amount of Oil Palm Production in Simalungun Regency Based on Data for 2000-2019 Using Double Exponential Smoothing Method - Nababan, Yosua Pernando; Pane, Rahmawati (Journal of Mathematics Technology and Education, 2022)
Economic growth in our country comes from various sectors, one of which is the agricultural and plantation sectors. This sector plays an important role in generating a source of foreign exchange for our country after the oil and gas mining sector through its commodity exports. The data used by the author in this final project is secondary data from the Central Bureau of Statistics of North Sumatra regarding oil palm production in Simalungun Regency. Quantitative analysis is used to determine the amount of oil palm production in Simalungun Regency which is predicted in 2020, 2021, and 2022, involving production patterns from 2000 to 2019 Then based on the amount of production data, the data is processed using quantitative time forecasting methods. series, namely Double Exponential Smoothing one parameter from Brown, by looking at the resulting error value, namely the Mean Absoute Percentage Error (MAPE) value. Based on forecasting results, the amount of oil palm production in Simalungun Regency in 2020 is 467,295.15 tons, the amount of oil palm production in Simalungun Regency in 2021 is 501,766.48 tons, in 2022 it is 536,237.81 tons. So the production of palm oil in Simalungun Regency increases from year to year, but there are times when it decreases not so drastically, so it can be concluded that the production of palm oil harvests in Simalungun Regency is increasing.